Foundation of Japanese Buddhism - Matsunaga, Daigan (Buddhist Books International, 1974)
Foundation of Japanese Buddhism, Vol. I: The Aristocratic Age and its successor, Foundation of Japanese Buddhism,.Readers might also consider following the presentation with Junjiro Takakusu's The Essentials of Buddhist Philosophy at their elbow -- a pithy, detailed classic on the subject. Comparable in value, scope, and importance to David Seyfort Ruegg's Literature of the Indian Madhyamaka School, this work is a must-have for serious students. Covers many topics, including early Japanese use of Indian and Chinese sources such as Madhyamaka, Yogacara, and Hua-Yen, and the formation and evolution of the Japanese forms of Tendai, Zen, Shigon, Shin, and Jodoshin.